Oleuropein Improves Cognitive Dysfunction and Neuroinflammation in Diabetic Rats through the PI3K/Akt/mTOR Pathway - Jianru Shang; Shan Che; Mingjie Zhu (Applied Bionics and Biomechanics)
Objective. To explore the effect and mechanism of oleuropein on cognitive dysfunction and neuroinflammation in diabetic rats. Method. A diabetic rat model was constructed using streptozotocin, and the diabetic rats were divided into 3 groups with different treatment for 4 weeks, named STZ group (gavaged with normal saline), STZ+LOE group (40 mg/kg oleuropein, and STZ+SITA group (30 mg/kg sitagliptin). The fasting blood glucose (FBG), fasting serum insulin levels, and HOMA-IR index were measured in rats. After the last treatment, the Morris water maze experiment was carried out, and the rats were first subjected to training experiments for 4 consecutive days; the escape latency, number of crossing platform quadrant intersections, time spent in the target quadrant, and swimming speed were recorded. Additionally, the malondialdehyde (MDA), myeloperoxidase (MPO) content, superoxide dismutase (SOD) activity, interleukin- (IL-) 1β, tumor necrosis factor (TNF-α), and phosphatidylinositol 3-kinases (PI3K)/threonine-protein kinase (Akt)/mTOR expression levels in rat hippocampus tissues were detected. Results. Oleuropein reduced insulin resistance, spatial learning, and memory ability in diabetic rats. It also could improve oxidative stress and inflammatory response and activate the PI3K/Akt/mTOR signaling pathway in hippocampus tissues. Conclusion. Oleuropein ameliorates cognitive dysfunction and neuroinflammation in diabetic rats by regulating the PI3K/Akt/mTOR signaling pathway.